The Association of EGFR Mutations with Stage at Diagnosis in Lung Adenocarcinomas - Cho, Jaeyoung (PLoS One, 2016)
BACKGROUND: The prognostic role of epidermal growth factor receptor (EGFR) mutations in patients with lung adenocarcinomas remains controversial and the association between EGFR mutations and stage at the time of the initial diagnosis is debatable. In this study, we evaluated the association of EGFR mutations with stage at diagnosis in lung adenocarcinomas. MATERIALS AND METHODS: We retrospectively analyzed 1004 consecutive patients who were diagnosed with lung adenocarcinomas and tested for EGFR mutations between June 2011 and December 2014. RESULTS: EGFR mutations were detected in 49.2% of 1004 patients with lung adenocarcinomas. In multivariable analysis, EGFR mutations were significantly associated with early stage disease (stage I to II) at diagnosis (odds ratio [OR], 0.65; 95% confidence interval [CI], 0.49–0.87; P = 0.003). When adjusted for age, sex, smoking status, and screening, the adjusted proportion of EGFR mutations significantly decreased according to stage. The adjusted proportions of EGFR mutations were 57.6% (95% CI, 51.7%–63.3%) for stage I, 47.9% (95% CI, 36.9%–59.0%) for stage II, 47.5% (95% CI, 39.6%–55.5%) for stage III, and 43.4% (95% CI, 38.3%–48.6%) for stage IV (P = 0.0082). CONCLUSIONS: The presence of EGFR mutations is significantly associated with early stage disease at initial diagnosis in lung adenocarcinomas after adjusting for age, sex, smoking status, and screening. This finding implies that EGFR mutations may play a role as a positive prognostic marker.